1999
DOI: 10.1084/jem.190.11.1549
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Lipid Rafts in B Cell Antigen Receptor Signaling and Antigen Targeting

Abstract: The B cell antigen receptor (BCR) serves both to initiate signal transduction cascades and to target antigen for processing and presentation by MHC class II molecules. How these two BCR functions are coordinated is not known. Recently, sphingolipid- and cholesterol-rich plasma membrane lipid microdomains, termed lipid rafts, have been identified and proposed to function as platforms for both receptor signaling and membrane trafficking. Here we show that upon cross-linking, the BCR rapidly translocates into gan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
392
5
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 437 publications
(439 citation statements)
references
References 51 publications
36
392
5
1
Order By: Relevance
“…Previous studies on whether CD45 translocates into LRs have yielded inconsistent results. The results of some studies have suggested that CD45 is excluded, while others have suggested that human leukemia cells and granulocytes transiently express CD45 in LRs (14,(31)(32)(33)(34). More recently, we observed that CD45 translocates into LRs in T cells from patients with SLE but not healthy controls (35).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Previous studies on whether CD45 translocates into LRs have yielded inconsistent results. The results of some studies have suggested that CD45 is excluded, while others have suggested that human leukemia cells and granulocytes transiently express CD45 in LRs (14,(31)(32)(33)(34). More recently, we observed that CD45 translocates into LRs in T cells from patients with SLE but not healthy controls (35).…”
Section: Discussionmentioning
confidence: 66%
“…Following engagement by antigen, the BCR complex translocates into cholesterol-and glycosphingolipidenriched plasma membrane microdomains known as lipid rafts (LRs), followed by phosphorylation by Src kinases. One theory suggests that LRs act as platforms for proximal signaling (13)(14)(15). In addition to translocated BCR, LRs carry Src protein tyrosine kinases (PTKs), glycosylphosphatidylinositol-anchored proteins, and heterotrimeric G proteins.…”
mentioning
confidence: 99%
“…It is of particular interest that the tyrosine phosphatase CD45 is specifically excluded from lipid rafts in B cells [27,36,43] and T cells [27,31,44]. While general molecular requirements for raft exclusion are not well understood, the CD45 transmembrane domain is sufficient to re-target otherwise raft-associated proteins to non-raft membranes.…”
Section: Discussionmentioning
confidence: 99%
“…31 In total, 10 mg each of biotin a-IgM and biotin a-CD19 or biotin rat IgG2a and biotin IgA were added and incubated for 30 min on ice. Avidin (5 mg/ml) was added for an additional 30 min on ice.…”
Section: Immunoprecipitationmentioning
confidence: 99%